La metáfora del “escenario” en la dinámica política y la valoración de la República parlamentaria en la lucha de clases en Francia y en los dieciocho brumarios de Luis Bonaparte de Karl Marx / The metaphor of the "stage" in the political dynamics and the valuation of the parliamentary republic in the class struggle in France and in the eighteenth brumaire by Louis Bonaparte of Karl Marx - BALSA, Javier (Utopía y Praxis Latinoamericana, 2019)
RESUMEN Este artículo analiza, en primer lugar, las consecuencias que tiene el uso de la metáfora del “escenario” para dar cuenta de la dinámica política, en La lucha de clases en Francia y en El Dieciocho Brumario de Luis Bonaparte de Marx. Más específicamente, estudia cuatro cuestiones: la entrada y la salida de actores, la reconfiguración del escenario por estos movimientos y por la constitución de bloques de alianzas, la incidencia de la arquitectura del escenario, y la lucha por significar los procesos y eventos políticos puntuales. En segundo lugar, el artículo analiza las valoraciones contradictorias del escenario de una “república parlamentaria” que contienen estos textos. ABSTRACT This article analyses, first, the consequences that has the employ of the metaphor of the “stage” to comprehend the political dynamic in The Class Struggles in France and The Eighteenth Brumaire of Louis Bonaparte of Marx. More specifically, it studies four questions: the entrance and the exit of actors, the reconfiguration of the stage caused by these movements and by the constitution of alliance blocks, the impact of the architecture of the stage, and the fight for signify the process and specific political events. Second, the article analyses the contradictory appraisals of the stage of a “parliamentary republic” that these texts have.